1999
DOI: 10.1016/s0035-9203(99)90078-0
|View full text |Cite
|
Sign up to set email alerts
|

Bancroftian filariasis in a paediatric population: an ultrasonographic study

Abstract: Little is known about lymphatic filariasis or the anatomical location of adult Wuchereria bancrofti in children. Seventy-eight children from Greater Recife, 23 microfilaria-positive and 55 microfilaria-negative in approximately 60 microL blood, underwent ultrasound examinations of the major superficial lymphatic vessels of the limbs, scrotal area (boys), and breast area (girls). The characteristic movements of adult worms, known as the filaria dance sign (FDS), were detected in 11 (14.1%) children. In 9 boys, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
0
2

Year Published

2000
2000
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(60 citation statements)
references
References 24 publications
2
56
0
2
Order By: Relevance
“…Though such studies have focused on adult-age populations, 3,4,10-12 we recently described the use of ultrasound to identify filarial worms in the lymphatics of children. 5 In that study of 11 parasitepositive children, most parasites were seen in pubertal or post-pubertal boys and were localized to the intrascrotal lymphatics, similar to that characteristically found in adult men.…”
Section: Introductionmentioning
confidence: 58%
See 1 more Smart Citation
“…Though such studies have focused on adult-age populations, 3,4,10-12 we recently described the use of ultrasound to identify filarial worms in the lymphatics of children. 5 In that study of 11 parasitepositive children, most parasites were seen in pubertal or post-pubertal boys and were localized to the intrascrotal lymphatics, similar to that characteristically found in adult men.…”
Section: Introductionmentioning
confidence: 58%
“…The development of techniques to diagnose infection much more sensitively than in the past by detecting antigen in the blood 1 and to identify subclinical lymphatic disease by ultrasonography [2][3][4] has led to the recognition that LF is a common infectious disease of children in endemic areas. 5 Disease associated with LF infection in children, however, is poorly understood. Although case reports attest to the occurrence in some children of the same LF manifestations commonly recognized in adults (e.g., elephantiasis, 6 hydrocele, 7 tropical pulmonary eosinophilia 8 ), these manifestations are not as frequent in children as they are in adults.…”
Section: Introductionmentioning
confidence: 99%
“…Por outro lado, dificilmente exibem doença clínica, exceto adenopatia 25 , apesar de a maior parte já apresentar doença subclínica evidenciada pela ultrassonografia 23 . Recomendamos que crianças e adolescentes apresentando manifestações clínicas, principalmente edema de membros e da genitália externa masculina, sejam avaliados por equipe multidisciplinar, para melhor definir a causa de sua doença, aventando-se entre os possíveis diagnósticos a possibilidade de malformação linfática congênita.…”
Section: Tratamento Quimioterápico Antifilarialunclassified
“…al. (22,23) had elegantly studied the characteristic movements of adult filarial worms known as filaria dance sign (FDS) by ultra sonographic study in scrotum and ditated lymphatics in subclinical hydroceles, tropical pulmonary eosinophilia (24) and more recently in scrotal and breast areas in children (25). Ultra sound findings often changed after therapy with DEC, with disappearance of dancing worms (26).…”
Section: Filarial Antibody and Antigen In Childrenmentioning
confidence: 99%
“…Recently ultrasonographic studies (25) have shown the presence of filarial worms in mf positive and mf negative children in filarial endemic areas emphasizing the importance of filariasis in children, the group which was neglected so far. SEVAFILACHEK using mf ES antigen for antibody and antigen assay was found to be very helpful in confirming fitaria aetiology and determining optimal DEC therapy along with judicial use of appropriate antibiotics, antihistaminics, analgesics etc.…”
Section: Immunomonitoring In Filaria Associated Clinical Manifestatiomentioning
confidence: 99%